Implementasi sistem absensi dan penggajian pada PT. Ophthalindo Jaya menggunakan metode Zachman - Muhammad Rozis Al Yasah; Sugiyono Sugiyono (Jurnal Manajamen Informatika Jayakarta, 2021)
This study aims to develop a system within the company at PT.Ophthalindo Jaya, which previously only relied on manual writing such as entry and exit permits, leave permits, sickness and so on, so that it has a very significant impact on the company to regulate employee activities at PT. Ophthalindo Jaya, Complaints or input. From some employees it is highly recommended to minimize the occurrence of negligence in making letters manually both internally and externally. This complaint is what makes the writer to find a solution so that the management becomes more dynamic in the operation of a company engaged in the medical device, The method that will be done is to create a way so that everyone can make it easier for employees to be more active in attendance and coordination with each department, a system that conducts attendance using an attendance card with a PHP-based program, with a data storage system. in MYSQL, as well as to make it easier for employees to access from outside, the author will also use CODEIGNITER to make it easier for users via mobile devices, so that this method can minimize the occurrence of errors in writing letters manually and monitor employee data more efficiently, so the problems that will arise are very minimize an error that can occur at any time.